Development of a functional and psychosocial evaluation toolkit using mixed methodology in a community-based physical activity program for childhood cancer survivors. - Shank, Jena; Chamorro-Viña, Carolina; Guilcher, Gregory M. T.; Schulte, Fiona; Culos-Reed, S. Nicole (Supportive Care in Cancer, 2022)
Purpose: The evidence demonstrating the benefits of exercise and PA in patients and survivors of childhood cancer has been translated into a handful of community-based programs, such as the Pediatric cancer patients and survivors Engaging in Exercise for Recovery Program (PEER). To support the translation of research to practice, the next step in knowledge translation is to evaluate program effectiveness. An evaluation must consider the goals of the PEER program, feedback from key stakeholders, and logistics of this program. Thus, the purpose of this study was to develop an evaluation toolkit with an algorithm for the implementation of the PEER program.Methods: Semi-structured interviews were conducted with three different groups (stakeholders in pediatric oncology, PEER parents, and PEER participants). The interviews were transcribed and coded by two independent reviewers.Results: Key themes extracted from the interviews were split into physical and psychosocial themes. The most reported psychosocial themes were quality of life (QOL), fatigue/energy levels, fun, and cs; and physical themes included motor skills, physical literacy, and physical activity levels. Tools were compiled into the evaluation based on key themes identified as well as logistics of PEER. An algorithm was developed to tailor the evaluation to participants based on age and mobility.Conclusion: To date, this is the first evaluation toolkit and algorithm developed for a specific community-based PA program, the PEER program. The next step in knowledge translation will be to implement the evaluation to assess feasibility and share the evaluation for adoption within other developing programs.